Strengthening the competence of dietetics students on providing nutrition care for HIV patients: application of attribution theory - Kusuma, Mutiara Tirta Prabandari Lintang (Kansas State University, 2017)
HIV and nutrition status are interrelated. Nutrition problems associated with HIV or its treatment occur in nearly all people living with HIV (PLHIV) and can be indicative of the stage and progression of infection. On the other hand, adequate nutrition ensures good nutrition status, immune function, improved treatment outcome, and quality of life. The growing problems of HIV and AIDS in Indonesia require health professionals, including dietitians, to mobilize for HIV care and control. However, studies have demonstrated health care workers to have prejudicial attitudes towards PLHIV, which may further jeopardize the quality of care. The objective of this study was to implement the attribution theory to improve HIV-related knowledge and attitudes among dietetics students. It is hypothesized that given the opportunity to revisit the antecedent of their stigma, dietetic students might be able to improve their attitudes and emotional reactions to HIV. Results from the cross-sectional study confirmed the attribution theory, showing that the stigmatizing attitudes were influenced by both personal values and environmental factors. The study also found that greater knowledge about HIV was associated with a better attitude toward PLHIV. This and the fact that universities differed in how they educated dietetic students about HIV, raise questions on the current dietetic curriculum in Indonesia and the teaching conduct in each dietetic school. These notions were studied in the second study, using a qualitative approach to inquire lecturers and school administrators. Four major themes emerged from the analysis confirming that HIV discourse in dietetic schools in Indonesia is very limited since it is not mandatory in the curriculum, lecturers are reluctant to talk about HIV, and there is apparent restriction to work with the key population. The way the lecturers attribute HIV with blames of personal responsibility and fear of contagion, heavily influence their teaching conduct. The intervention model with transformative learning supported the hypothesis that given the opportunity to reflect and re-question their judgment, students were able to improve their knowledge and reduce their stigmatizing attitudes. Overall, these studies give a warning to policy makers in health and education sectors as well as the school administrators that dietetics students have negative attitudes towards PLHIV and this stigma is associated with lack of knowledge about HIV, hence the need to improve response from both sectors. This study also serves as a strong call to provide more opportunities to students to learn about HIV and to reach out to the patients and key population to instill better understanding and acceptance to HIV.
Keywords: HIV; AIDS; Dietetic students; Nutrition care; Attribution theory; Transformative learning theory